PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN KONSENTRASI KEPEMILIKAN TERHADAP PERSISTENSI LABA - DUDI PRATOMO; ATHIYYA NADHIFA NURAULIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Earnings Persistence is a revision of earnings to see company sustainable profits, this become an important aspect in earnings information for decision making.Population in this study used property, real estate and construction companies listed on the Indonesia Stock Exchange in 2013-2017. The total sample of the study were 17 companies. Data analysis using multiple linear regression and the process used software eviews 10. Results this study indicate that together institutional ownership, manageriall ownership and ownership concentration as well as the level of debt and company size affect earnings persistence with a coefficient of determination of 30.18%. Partial test shows that institutional ownership, managerial ownership, ownership concentration and company size negatively affect earnings persistence while the level of debt does not affect earnings persistence.